Is Environmental Kuznets Curve (EKC) Still Relevant? - Gill, Abid Rashid; Viswanathan, Kuperan K.; Hassan, Sallahuddin (International Journal of Energy Economics and Policy, 2017)
The main purpose of this study is to evaluate the relevancy of Environmental Kuznets Curve (EKC) hypothesis to the environment problem of today world. According to EKC hypothesis, continuous economic growth eventually reverses the environmental degradation created at the early stage of economic development. This hypothesis emerged in the 1990s and led many serious commentators of economic development to assume that developing countries should focus on economic growth and any environmental problem would be automatically solved by the process of economic growth. The necessary message of EKC was “grow now clean later”. The empirical studies on EKC lead to the conclusion that EKC transition exists only for local pollutants. We found that EKC empirical literature is not econometrically sound and the relationship of many types of pollutants with income has not been tested yet due to the non-availability of data. We also conclude that EKC transition is not Pareto efficient and EKC growth strategy is resource intensive and has huge environmental cost that this planet may not be able to absorb in future. The Key recommendations of the study are that developing world should follow different growth path than that of EKC. They should choose a growth path that is not detrimental to the environment so that stock of pollution created by advanced countries can be contained and advanced countries should make green technologies affordable to developing countries. Keywords: Environment Degradation, Sustainable development, Local and Global pollutants, Green Technologies, Pareto Efficient. JEL Classifications: Q50, Q54, Q55, Q58